2015
DOI: 10.1093/schbul/sbu222
|View full text |Cite
|
Sign up to set email alerts
|

Nonverbal Social Communication and Gesture Control in Schizophrenia

Abstract: Schizophrenia patients are severely impaired in nonverbal communication, including social perception and gesture production. However, the impact of nonverbal social perception on gestural behavior remains unknown, as is the contribution of negative symptoms, working memory, and abnormal motor behavior. Thus, the study tested whether poor nonverbal social perception was related to impaired gesture performance, gestural knowledge, or motor abnormalities. Forty-six patients with schizophrenia (80%), schizophrenif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
121
4
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 105 publications
(148 citation statements)
references
References 58 publications
(100 reference statements)
12
121
4
4
Order By: Relevance
“…In the light of these findings, it is likely that inefficient gesture performance may contribute to impaired social functioning and functional outcome. Given that poor social perception impaired gesture performance [17], poor gesture performance in first-episode patients may result from poor social cognition at the very onset of the disorder. In fact, deficits in social cognition were reported even before the actual onset of psychosis, for instance in adolescents at risk for psychosis [48], and may already substantially impact social functioning in first-episode patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the light of these findings, it is likely that inefficient gesture performance may contribute to impaired social functioning and functional outcome. Given that poor social perception impaired gesture performance [17], poor gesture performance in first-episode patients may result from poor social cognition at the very onset of the disorder. In fact, deficits in social cognition were reported even before the actual onset of psychosis, for instance in adolescents at risk for psychosis [48], and may already substantially impact social functioning in first-episode patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was shown that pantomiming meaningless gestures was particularly disturbed [15], which is associated with poor frontal lobe function [16]. Furthermore, disturbed nonverbal social perception is linked to poor gesture performance in schizophrenia [17]. …”
Section: Introductionmentioning
confidence: 99%
“…fMRI studies suggest the existence of similar domain-specific long-range connections between specialized cortical regions and the limbic system, e.g., for emotional face processing, between the fusiform gyrus, the amygdala, and the orbitofrontal cortex [23, 24]. In the motor domain, the capacity to recognize nonverbal information such as hand gestures is strongly linked to the performance of hand gestures [25], suggesting a parallel organization with direct connections between brain areas of action perception and those of action planning [26]. The cortical connections of the motor system include areas of executive control and action planning (rostral to primary motor cortex) and parietal areas of action perception (see right panel of Fig.…”
Section: Outline Of Synopsismentioning
confidence: 99%
“…Two studies noted an association of impaired gesture performance with frontal lobe dysfunction and motor abnormalities in schizophrenia [25, 126]. In addition, patients have problems interpreting the hand gestures of others correctly [129].…”
Section: Mapping Symptoms Onto Brain Systems: Empirical Evidence For mentioning
confidence: 99%
See 1 more Smart Citation